1990
DOI: 10.1038/344682a0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional silencing and thermoregulation of gene expression in Escherichia coli

Abstract: Expression of specific adhesive properties by bacteria in general seems to be regulated to fit the environmental conditions. An example is the transcriptional regulation of digalactoside-specific binding by uropathogenic strains of Escherichia coli. The fimbrial structures (pili) on the bacterial surface carry the adhesin and are present during growth at 37 degrees C but are not produced by cells at lower temperatures, such as 25 degrees C. Thermoregulation of expression is due to temperature-dependent transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
194
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 301 publications
(204 citation statements)
references
References 29 publications
9
194
0
1
Order By: Relevance
“…Growth of E. coli in glucose reduces the OFF to ON switch rate by 35-fold as a result of lowered cAMP level, which prevents CAP-dependent activation of papBA and subsequent papI transcription (23). Pap pilin transcription is also significantly repressed by growth at low temperature (Ͻ26°C) (27,28) and rich medium (LB broth) (7). It is not clear whether these growth conditions directly alter the phase switch itself or alternatively inhibit pap transcription in phase ON cells.…”
Section: Switch Inputsmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth of E. coli in glucose reduces the OFF to ON switch rate by 35-fold as a result of lowered cAMP level, which prevents CAP-dependent activation of papBA and subsequent papI transcription (23). Pap pilin transcription is also significantly repressed by growth at low temperature (Ͻ26°C) (27,28) and rich medium (LB broth) (7). It is not clear whether these growth conditions directly alter the phase switch itself or alternatively inhibit pap transcription in phase ON cells.…”
Section: Switch Inputsmentioning
confidence: 99%
“…However, this 15.5-kDa global regulatory protein does modulate Pap phase switching, and appears to play an essential role in the repression of Pap expression by environmental signals including low temperature (27). At temperatures below 26°C, H-NS appeared to bind to the pap regulatory region as evidenced by methylation protection of the two pap GATC sites (6).…”
Section: Role Of H-nsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may act as a negative regulator of transcription (40,41), functioning by "transcriptional silencing" (42) and "repression via DNA topology" (41, 43) through oligomeric binding to DNA. Three putative functional domains have been identified in b Superinfection immunity (Imm.)…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism is not clear. There is no difference in the level of hns mRNA and therefore presumably no difference in the concentration of H-NS protein in the relevant temperature range (Gö ransson et al, 1990;Colonna et al, 1995;Sondé n and Uhlin, 1996). In Shigella flexneri, where the expression of the invasion regulatory gene, virB, at 30ЊC is less than 1/20th of that at 37ЊC, it has recently been shown that this thermoregulation is dependent on the superhelicity of the virB promoter and is not mediated by H-NS (Tobe et al, 1995).…”
Section: H-ns and Temperature Regulationmentioning
confidence: 99%